Impact of correction factors in human brain lesion‐behavior inference. Issue 3 (3rd January 2017) - Sperber, Christoph; Karnath, Hans‐Otto
Abstract: Statistical voxel‐based lesion‐behavior mapping (VLBM) in neurological patients with brain lesions is frequently used to examine the relationship between structure and function of the healthy human brain. Only recently, two simulation studies noted reduced anatomical validity of this method, observing the results of VLBM to be systematically misplaced by about 16 mm. However, both simulation studies differed from VLBM analyses of real data in that they lacked the proper use of two correction factors: lesion size and "sufficient lesion affection." In simulation experiments on a sample of 274 real stroke patients, we found that the use of these two correction factors reduced misplacement markedly compared to uncorrected VLBM. Apparently, the misplacement is due to physiological effects of brain lesion anatomy. Voxel‐wise topographies of collateral damage in the real data were generated and used to compute a metric for the inter‐voxel relation of brain damage. "Anatomical bias" vectors that were solely calculated from these inter‐voxel relations in the patients' real anatomical data, successfully predicted the VLBM misplacement. The latter has the potential to help in the development of new VLBM methods that provide even higher anatomical validity than currently available by the proper use of correction factors. Hum Brain Mapp 38:1692–1701, 2017 . © 2017 Wiley Periodicals, Inc.